Betrayal trauma and adult mental health: The role of mentalizing and dissociation - Monika Olga Jańczak; Giulia Gagliardini; Anna Kamza; Antonello Colli; Peter Fonagy; Tobias Nolte (PLoS ONE, 2026)
Background Trauma experienced across the lifespan has been linked to a wide range of adverse mental health outcomes. However, the psychological mechanisms connecting betrayal trauma to later psychopathology remain insufficiently understood. Objective This cross-sectional study investigated associations between betrayal trauma during childhood and adulthood and adult psychopathology—specifically depressive symptoms and level of personality functioning within a dimensional model of personality disorders. We tested a path model examining direct and indirect associations between betrayal trauma at different developmental periods and adult psychopathology via dissociation and hypomentalizing. Participants A sample of 209 adults (61% female; aged 18–45 years; M = 29.7, SD = 7.88) were recruited from community and clinical settings in Poland. Methods Participants completed validated self-report measures assessing betrayal trauma, depressive symptoms, personality functioning (ICD-11 model), dissociation, and mentalizing. Path analyses with parallel mediation were conducted using Satorra–Bentler estimation and 5,000 bootstrap resamples to examine both direct and indirect associations. Results Both childhood and adulthood betrayal trauma were significantly associated with depressive symptoms and PD severity through dissociation and hypomentalizing [χ²(6) = 13.68, p = .033; CFI = 0.989; TLI = 0.931; RMSEA = 0.078; SRMR = 0.038]. No significant direct effects were observed once psychological processes were included. Mentalizing consistently demonstrated a stronger indirect association than dissociation across models. Adulthood betrayal trauma showed a greater total effect on depressive symptoms (β = .30; p < .001) than childhood trauma (β =  .17; p = .043), whereas their effects on personality pathology were comparable (respectively, β =  .21; p = .006 for adult trauma and β = .22; p = .008 for childhood trauma). For adulthood trauma and PD severity, the direct association was small and non-significant (β = −.06), whereas indirect effects via dissociation (β = .11) and mentalizing (β = .16) were positive, resulting in a positive total effect. Conclusions These findings indicate that the link between betrayal trauma and adult psychopathology may be best conceptualised in terms of co-occurring psychological processes rather than direct exposure effects. Hypomentalizing, in particular, appears to represent a key transdiagnostic mechanism connecting relational trauma across developmental stages with both mood and personality pathology.